Educational Authority in Prevention of Bullying at SMP Negeri 23 Kerinci: A Family Law Perspective in Indonesia - Dian Eka Satria; Widya Yul (ISLAMIKA, 2026)
Although bullying prevention has received increasing attention in educational research, limited empirical work has examined it through the integrated perspectives of educational authority, Islamic family law values, and multi-stakeholder governance. This study analyzes the social-structural manifestations of bullying, the role of educational authority in anti-bullying policy formulation and implementation, the institutionalization of Islamic family law values as a preventive strategy, and the dynamics of multi-stakeholder collaboration in bullying prevention governance at SMP Negeri 23 Kerinci, Jambi. Employing a qualitative case study design, the research involved 25 purposively selected participants, including school leaders, teachers, students, parents, and external stakeholders. Data were collected through semi-structured interviews, non-participant observations, and document analysis, and analyzed using interactive thematic analysis. The findings indicate that bullying is predominantly manifested in non-physical and relational forms embedded in normalized peer interactions and weakly supervised spaces. Educational authority is exercised largely through bureaucratic compliance and reactive responses, thereby limiting its preventive effectiveness. Islamic family law values, such as rahmah, amanah, and ukhuwah, are morally influential but remain informally practiced and insufficiently institutionalized within school governance structures. In addition, weak, procedural, and incident-based collaboration among schools, families, and local government actors constrains shared accountability and undermines sustainable prevention efforts. The study concludes that bullying prevention constitutes a systemic governance challenge that requires the integration of proactive educational authority, the formal institutionalization of moral-legal values, and sustained multi-stakeholder synergy. These findings contribute to value-based and institutional approaches to bullying prevention while offering practical implications for policy development and collaborative school governance.